Analisis Efisiensi Teknis dan Faktor Penentunya pada Usahatani Kentang (Solanumtuberosum L.) di Kota Pagar Alam, Provinsi Sumatera Selatan - M. Agus Maryanto; Ketut Sukiyono; Basuki Sigit Priyono (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
This study aims to determine and analyse the level of technical efficiency and the factors influencing technical efficiency of a potato farming in North Dempo, sub-district Pagar Alam City, South Sumatera Province using 51 farmers who are censused. Frontier production function, estimated using the MLE method, is used to determine the level of technical efficiency. Meanwhile, multiple regression estimated using OLS approach is used to determine factors influencing technical efficiency level. The research showed that, land area, seed, organic fertilizer, ZA fertilizer, Ponska fertilizer, and fungiside were significantly affect potato production. The research finds that the level of technical efficiency of potato farming was, on the average, 81.336 percent. The research also shows that the intensity of extension and farmers’ experience affect significantly and negatively technical inefficiency while formal education, age, and land ownership status do not.